Inflammatory breast cancer Clinical presentation Value of combined treatments - Viola Alles, Alberto; Sabini, Graciela; Barrios, Enrique; Musé, Miguel (Cirugía del Uruguay, 1995)
Over a total of 1152 patients carrying breas/ cancer who were treated between 1978 and 1988, 41 cases (3,5%) corresponded to the inf/ammatory variety Their ages ranged between 26 and 73 years; 15 (63,5 %) were found in postmenopausica/ women. From the clinical point of view, in 34, 1 % of the cases the disease was limited to the breast exclusive/y; 48, 7% presented regional invasion of nades and the remainig 17% presented disseminated disease. lnitial treatment consisted of 3-4 chemotherapy cycles of the FAC type except in the case of elderly patients who a/so received CMF association. Al/ of them were la ter radiated with doses of 5000-6000 cGy over breas/ and nade territories. Treatment ended with 6 to 8 additional chemoterapy cycles. None of the patients underwent surgery. Median survival of the whole population was of 22 months (26 far premenopausica/ patients and 15 far the postmenopausical ones). Recidive percentage rose as 30%, 45% of the localized forms disseminated in the evolution. The authors emphasize the fact that the therapeutical strategy was based on chemo-radiotherapy association; there is a possibility of management with high doses of cytostatic agents with or without bone marrow transplant.